Metodologi Pemahaman Hadist Islamologi dan Ulama Kontemporer (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
One of methods formulated by comtemporary Ulama to approach hadith is  ikhtilaf hadith. This method could be developed become frame of maudu‟i understanding. Using this method in analyzing cases in hadith is expected to  prevent ignorance in summarizing process. If understanding is being trapped in  tarjih al hadith, which is historical, one may be trapped in the method, tarjih al  hadits, trough analyzing sanad. While in fact, the tarjih theonly one method  within the process of hadith, which is seen contradictive (ikhtilaf)